SEMA7AR148W mutation promotes lipid accumulation and NAFLD progression via increased localization on the hepatocyte surface - Nan Zhao; Xiaoxun Zhang; Jingjing Ding; Qiong Pan; Ming-Hua Zheng; Wen-Yue Liu; Gang Luo; Jiaquan Qu; Mingqiao Li; Ling Li; Ying Cheng; Ying Peng; et al. (JCI Insight, 2022)
Genetic polymorphisms are associated with the development of nonalcoholic fatty liver disease (NAFLD). Semaphorin7a (Sema7a) deficiency in mouse peritoneal macrophages reduces fatty acid (FA) oxidation. Here, we identified 17 individuals with SEMA7A heterozygous mutations in 470 patients with biopsy-proven NAFLD. SEMA7A heterozygous mutations increased susceptibility to NAFLD, steatosis severity, and NAFLD activity scores in humans and mice. The Sema7aR145W mutation (equivalent to human SEMA7AR148W) significantly induced small lipid droplet accumulation in mouse livers compared with WT mouse livers. Mechanistically, the Sema7aR145W mutation increased N-glycosylated Sema7a and its receptor integrin β1 proteins in the cell membranes of hepatocytes. Furthermore, Sema7aR145W mutation enhanced its protein interaction with integrin β1 and PKC-α and increased PKC-α phosphorylation, which were both abrogated by integrin β1 silencing. Induction of PKCα_WT, but not PKCα_dominant negative, overexpression induced transcriptional factors Srebp1, Chrebp, and Lxr expression and their downstream Acc1, Fasn, and Cd36 expression in primary mouse hepatocytes. Collectively, our findings demonstrate that the SEMA7AR148W mutation is a potentially new strong genetic determinant of NAFLD and promotes intrahepatic lipid accumulation and NAFLD in mice by enhancing PKC-α–stimulated FA and triglyceride synthesis and FA uptake. The inhibition of hepatic PKC-α signaling may lead to novel NAFLD therapies.